Quantitative retrospective natural history modeling of WDR45-related developmental and epileptic encephalopathy: a systematic cross-sectional analysis of 160 published cases - Saffari, Afshin; Schröter, Julian; Garbade, Sven; Alecu, Julian E.; Ebrahimi-Fakhari, Darius; Hoffmann, Georg F.; Kölker, Stefan; Ries, Markus; Syrbe, Steffen (Autophagy, 2022)
WDR45-related neurodevelopmental disorder (NDD) is a clinically-heterogenous congenital disorder of macroautophagy/autophagy. The natural history of this ultra-orphan disease remains incompletely understood, leading to delays in diagnosis and lack of quantifiable outcome measures. In this cross-sectional study, we model quantitative natural history data for WDR45-related NDD using a standardized analysis of 160 published cases, representing the largest cohort to date. The primary outcome of this study was survival. Age at disease onset, diagnostic delay and geographic distribution were quantified as secondary endpoints. Our tertiary aim was to explore and quantify the spectrum of WDR45-related phenotypes. Survival estimations showed low mortality until 39 years of age. Median age at onset was 10 months, with a median diagnostic delay of 6.2 years. Geographic distribution appeared worldwide with clusters in North America, East Asia, Western Europe and the Middle East. The clinical spectrum was highly variable with a bi-phasic evolution characterized by early-onset developmental and epileptic encephalopathy during childhood followed by a progressive dystonia-parkinsonism syndrome along with cognitive decline during early adulthood. Female individuals showed milder disease severity. The majority of pathogenic WDR45 variants were predicted to result in a loss of WDR45 expression, without clear genotype-phenotype associations. Our results provide clinical and epidemiological data that may facilitate an earlier diagnosis, enable anticipatory guidance and counseling of affected families and provide the foundation for endpoints for future interventional trials.Abbreviations: BPAN: beta-propeller protein-associated neurodegeneration; CNS: central nervous system; DEE: developmental and epileptic encephalopathy; MRI: magnetic resonance imaging; NBIA: neurodegeneration with brain iron accumulation; NDD: neurodevelopmental disorder; NGS: next-generation sequencing; WDR45/WIPI4: WD repeat domain 45
Online veröffentlicht: 24. November 2021
Gesehen am 11.10.2022